1994
DOI: 10.1038/bjc.1994.461
|View full text |Cite
|
Sign up to set email alerts
|

DT-diaphorase protects cells from the hypoxic cytotoxicity of indoloquinone EO9

Abstract: Summary Aerobic sensitivity to indoloquinone E09 has been shown to correlate with cellular levels of the two-electron reducing enzyme DT-diaphorase. However, little is known about the relative roles of one-and two-electron reducing enzymes in the hypoxic cytotoxicity of E09. We have characterised a panel of 23 human tumour cell lines for both bioreductive enzyme activities and aerobic sensitivity to E09. Eight cell lines were then selected for a comparison of aerobic and hypoxic sensitivities. Activities of DT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 26 publications
0
29
1
Order By: Relevance
“…Methods reported in the literature do not appear to have been validated, i.e. the non-dicoumarol-inhibitable reduction of cytochrome c (Segura-Aguilar et al, 1990) or the NADHdependent reduction of cytochrome c (Plumb et al, 1994), and assume that cytochrome b5 reductase is the only enzyme responsible for the NADH-dependent reduction of cytochrome c. Our data indicate that this assumption is not valid. From Figure 4 it is evident that cytochrome b5 reductase activity does not account for all of the NADH-dependent reduction of cytochrome c in any cell line, as assessed using pHMB as a selective inhibitor.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…Methods reported in the literature do not appear to have been validated, i.e. the non-dicoumarol-inhibitable reduction of cytochrome c (Segura-Aguilar et al, 1990) or the NADHdependent reduction of cytochrome c (Plumb et al, 1994), and assume that cytochrome b5 reductase is the only enzyme responsible for the NADH-dependent reduction of cytochrome c. Our data indicate that this assumption is not valid. From Figure 4 it is evident that cytochrome b5 reductase activity does not account for all of the NADH-dependent reduction of cytochrome c in any cell line, as assessed using pHMB as a selective inhibitor.…”
Section: Discussioncontrasting
confidence: 45%
“…For example, the levels of DTdiaphorase have been shown to vary 10 000-fold in a panel of 23 tumour cell lines (Robertson et al, 1994) and also to be elevated in tumour tissue compared with surrounding noncancerous tissue (Riley and Workman, 1992). The aerobic toxicity of the indoloquinone E09 correlates highly with intracellular DT-diaphorase activity (Plumb et al, 1994;Robertson et al, 1994). Therefore, E09 should be targeted at tumours with high levels of DT-diaphorase, and would be expected to be of litle or no therapeutic benefit when used as a single agent to treat tumours with low DT-diaphorase levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The similar DNA damage and sensitivity of each of the human and each of the murine cell lines suggests that they must possess similar levels of activity of the reductase(s) that activates tirapazamine to a cytotoxic species. However, in the clinic, wide variations in reductase activity, as has been reported for human tumour cell lines (Plumb et al, 1994;Robertson et al, 1994), and varying levels of hypoxia , would be expected to result in large differences in sensitivity to tirapazamine. It is of primary importance that in this study, by measuring DNA damage, it was possible to distinguish between cell lines with 2-to 3-fold differences in sensitivity to killing by tirapazamine under hypoxic conditions.…”
Section: Cytotoxicitymentioning
confidence: 98%
“…The response of a tumour to any such bioreductive drug will depend both on the level of activity of the reductase(s) that activate the drug to a cytotoxic species, and the level of tumour hypoxia. Recent studies have shown that reductase activity can vary substantially between different human tumour cell lines (Plumb et al, 1994;Robertson et al, 1994), and measurements made using oxygen electrodes show large variations in oxygen tensions between tumours . It would therefore be highly desirable to be able to predict the response of individual tumours to a bioreductive drug so that patients unlikely to benefit from the drug would not be treated with it, and further, the power of a clinical trial of the drug to produce a significant response would be improved.…”
mentioning
confidence: 99%